Do other ethnics have the same complete denture biometric-guides as Caucasians? - Mustafa, Ammar A.; Abdul Majeed, Kais Raad (2013)
To compare the applicability of biometric guides used in clinical and lab procedures of complete denture construction on different ethnic origins. Three hundred volunteers from three different ethnic origins (Malay, Chinese and Indians) with age range from 20 to 75 years-old were volunteered to participate in this study as test groups. The control group was consisted of 100 Caucasians volunteers with age range 21–66 years-old. Ethical committee approval was obtained from our University. In this comparative cross sectional descriptive and analytical study all patients were presented with natural incisors and canines. Measurements were performed to the width of the nostrils and the inner-canthus distance by digital caliper and compared to the width of the six upper anterior teeth and to both the width of the upper two centrals and the philtrum respectively. Alginate impression were made to all patients. Two lines were made from the centre of incisive papilla to the facial surfaces of the central incisors another line was made to the tip of the left and right canines. The distance from midpoint of incisive papilla to these three lines were measured on study casts. Statistical analyses were performed using SPSS 16 software. The comparative results showed highly significant relations among comparative variables. No significant differences found among groups (p > 0.005). Biometric guides are applicable to most ethnic origins. Thus, they are important clues to be used significantly in both clinical and lab procedures of complete denture construction.